2014
DOI: 10.3758/s13420-014-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spatial learning in the partially baited radial-arm maze task between commonly used rat strains: Wistar, Spargue-Dawley, Long-Evans, and outcrossed Wistar/Sprague-Dawley

Abstract: Strain-related differences in animals' cognitive ability affect the outcomes of experiments and may be responsible for discrepant results obtained by different research groups. Therefore, behavioral phenotyping of laboratory animals belonging to different strains is important. The aim of the present study was to compare the variation in allothetic visuospatial learning in most commonly used laboratory rat strains: inbred Wistar (W) and Sprague-Dawley (SD), outcrossed Wistar/Sprague-Dawley (W/SD), and outbred L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…These outperform Sprague–Dawley and Long–Evans rats, even though albino Wistar rats are known to have worse visual functions than pigmented rats (including lower visual acuity and impaired vision). Such findings indicate that in small rodents, high visual acuity is not required for successful performance in visuospatial tasks where the visual cues are at a distance of 1.5–2 m (Gökçek-Saraç et al 2015 ). The most popular strains used for BM are Wistar rats (Gawel et al 2016 ; Trofimiuk and Braszko 2011 ; Vargas-Lopez et al 2011 ) and Sprague–Dawley rats (McAteer et al 2016 ; Locklear and Kritzer 2014 ).…”
Section: Test Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These outperform Sprague–Dawley and Long–Evans rats, even though albino Wistar rats are known to have worse visual functions than pigmented rats (including lower visual acuity and impaired vision). Such findings indicate that in small rodents, high visual acuity is not required for successful performance in visuospatial tasks where the visual cues are at a distance of 1.5–2 m (Gökçek-Saraç et al 2015 ). The most popular strains used for BM are Wistar rats (Gawel et al 2016 ; Trofimiuk and Braszko 2011 ; Vargas-Lopez et al 2011 ) and Sprague–Dawley rats (McAteer et al 2016 ; Locklear and Kritzer 2014 ).…”
Section: Test Subjectsmentioning
confidence: 99%
“…In summary, strain-related differences in animal performance in cognitive tasks cannot be underestimated since such differences may affect the outcomes of the experiment (Gökçek-Saraç et al 2015 ).…”
Section: Test Subjectsmentioning
confidence: 99%
“…The aim of the present study was to merge the rich literature of rat social behavior studies [ 26 33 ], with the demand for high-throughput behavioral assays amenable to preclinical ASD models [ 34 ]. We elected to establish our behavioral testing approach in two commonly used strains of laboratory rats—the albino Sprague-Dawley (SD) and pigmented Long-Evans (LE) that exhibit strain specific patterns of behavior [ 35 39 ]. Numerous studies have documented differences in social interactions among rat strains [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this last point, a previous study in our lab, using the same cues, apparatus and level of illumination as in the present study, showed that the performance of Wistar rats in a reference spatial memory task was more affected by a change in the general shape of the experimental room than by the removal of salient cues (Ramos, ). Third, that high visual acuity is not a prerequisite to successful performance in spatial tasks has been directly demonstrated in a recent study (Gökçek‐Saraç et al, ). In this study different rat strains, albino (Wistar, Sprague‐Dawley), pigmented (Long‐Evans) and outcrossed (Wistar/Sprague‐Dawley) were compared in allocentric visual‐spatial learning.…”
Section: Discussionmentioning
confidence: 89%